Harmoni Adat dan Syariat: Analisis Pembagian Warisan Adat Pepadun Lampung dalam Perspektif Khi: Harmony Of Customary and Sharia: An Analysis of the Division of Inheritance in Pepadun Lampung from a Khi Perspective - Alfarizi, Zaidan; Mahmudi, Zaenul (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This research aims to harmonize the provisions of customary law and Sharia in the inheritance distribution system, so as to create balance and harmony in its application. Indonesia allows people to choose the division of inheritance through 3 perspectives, namely Islamic law, customary law and civil law. In the distribution of customary law, there are customary societies that use the Patrilineal-majorate principle in the inheritance distribution scheme, this occurs in the Pepadun Lampung customary society. The problem that occurs in the field is when faced with two different inheritance systems, namely customary law or Sharia law. Therefore, it is necessary to take steps to harmonize the customary law that lives in the community with Sharia law. The problem formulated in this research is to review the solution to harmonize the inheritance distribution practices of the Pepadun Lampung customary community using the perspective of the Compilation of Laws. This research uses empirical research with an anthropological approach. Using an anthropological approach allows this study to contribute in helping to identify factors that enable harmony between customary laws and Islamic law in the division of inheritance. Primary data sources come from interviews with traditional leaders, field observations and documentation. The conclusion of this research is that there are facts related to the principle of obeying parents which is the basis for the distribution of inheritance in the Pepadun customary society. This principle can be used as an effort to harmonize culture and Sharia (which is listed in the Compilation of Islamic Law).